Probingintermediate-mass black holes in M87 through multiwavelength gravitational wave observations. Issue 1 (16th May 2020) - Emami, Razieh; Loeb, Abraham
ABSTRACT: We analyse triple systems composed of the supermassive black hole (SMBH) near the centre of M87 and a pair of black holes (BHs) with masses in the range of 10-10^3 M_ . We consider the post Newtonian precession as well as the Kozai–Lidov interactions at the quadruple and octupole levels in modelling the evolution of binary black hole (BBH) under the influence of the SMBH. Kozai–Lidov oscillations enhance the gravitational wave (GW) signal in some portions of the parameter space. We identify frequency peaks and examine the detectability of GWs with LISA as well as future observatories such as μAres and DECIGO. We show examples in which GW signal can be observed with a few or all of these detectors. Multiwavelength GW spectroscopy holds the potential to discover stellar to intermediate mass BHs near the centre of M87. We estimate the rate, Γ, of collisions between the BBHs and fly-by stars at the centre of M87. Our calculation suggest Γ 10 Gyr^-1 for a wide range of the mass and semimajor axes of the inner binary.